2020
DOI: 10.7554/elife.51185
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein L-1 renal risk variants form active channels at the plasma membrane driving cytotoxicity

Abstract: Recently evolved alleles of Apolipoprotein L-1 (APOL1) provide increased protection against African trypanosome parasites while also significantly increasing the risk of developing kidney disease in humans. APOL1 protects against trypanosome infections by forming ion channels within the parasite, causing lysis. While the correlation to kidney disease is robust, there is little consensus concerning the underlying disease mechanism. We show in human cells that the APOL1 renal risk variants have a population of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(88 citation statements)
references
References 70 publications
13
75
0
Order By: Relevance
“…In agreement with this model, cation channel formation by recombinant human APOL1 requires acidic pH (as in endosomes), whereas channel opening requires subsequent pH neutralization (as in recycling to the plasma membrane) (14,15). APOL1 G1 and G2 expression in podocytes and immortalized cell lines also causes cytoplasmic swelling, which is proposed to result from dysregulated APOL1 channel activity at the plasma membrane (16,17).…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…In agreement with this model, cation channel formation by recombinant human APOL1 requires acidic pH (as in endosomes), whereas channel opening requires subsequent pH neutralization (as in recycling to the plasma membrane) (14,15). APOL1 G1 and G2 expression in podocytes and immortalized cell lines also causes cytoplasmic swelling, which is proposed to result from dysregulated APOL1 channel activity at the plasma membrane (16,17).…”
mentioning
confidence: 63%
“…Instead, our data further support the notion that endocytic recycling of APOL1 drives lysis of trypanosomes via the pH-dependent opening of APOL1 cation channels in the parasite plasma membrane. Intriguingly, Giovinazzo et al (17) recently reported that induction of human cell swelling and lysis by APOL1 renal risk variants depends on a nonselective cation influx at the plasma membrane. We anticipate that the mutants described herein will allow us to further investigate the precise role of APOL1 cation channels in trypanolysis, as well as the potential role of APOL1 cation channel formation in the development of cytotoxicity caused by APOL1 renal risk variants.…”
Section: Discussionmentioning
confidence: 99%
“…APOL1 is a membrane-associated protein with several putative transmembrane domains 21,[56][57][58] and localizes to multiple cellular membrane environments, including endo-lysosomes, golgi-ER, mitochondria and plasma membranes. 14,20,23,31,32,[34][35][36]55,[58][59][60][61] In this membrane environment, full length APOL1 proteins, especially the G1 and G2 formed large molecular weight oligomers as judged by native non-reducing PAGE. Such oligomers may mediate cellular cascade leading to cytotoxicity.…”
Section: Structure-function Correlation Of Apol1 Variants: Why Is It mentioning
confidence: 99%
“…12 c ApoL1-mediated cytotoxicity is reported to result from cationic pore formation at the plasma membrane. 1,11,13 Because podocytes secrete apoL1 11 However, given its dependence on acidic pH for membrane insertion, in order to generate surface pores apoL1 must travel through the endocytic pathway and be recycled back to the plasma membrane. 14 Because independent studies did not detect apoL1 in the endocytic pathway, this hypothesis can be ruled out.…”
mentioning
confidence: 99%
“…2,11,15 Moreover, if apoL1 recycling to the plasma membrane can tentatively be envisaged to explain trypanosome lysis, 14 this process is difficult to justify in podocytes, and does not explain why the G1 or G2 variants would trigger toxic pore activity. 13 Conversely, reducing Golgi PI(4)P levels can affect cation transport at the cell surface. 16 I propose that kidney disease results from cellular reorganization induced by apoL1-mediated inactivation of apoL3 that, via PI4KB, controls both vesicular trafficking at the Golgi (Figure 1, hit 1) and membrane fusion activities at ERmitochondrion contact sites (MERCs) (Figure 1, hit 2).…”
mentioning
confidence: 99%